Identification of pathogens causing invasive fungal rhinosinusitis in surgical biopsies using polymerase chain reaction - S. Chaturantabut (2020)
Copyright © The Author(s), 2020. Published by Cambridge University Press. BackgroundInvasive fungal rhinosinusitis is associated with high morbidity and mortality. Rapid pathogen identification is mandatory, but fresh tissue is not always available. A polymerase chain reaction method was designed in order to detect fungi in formalin-fixed paraffin-embedded samples. This was applied to a retrospective series of tissue biopsies from Thai patients with invasive fungal rhinosinusitis.MethodsTissue blocks from 64 cases yielded adequate DNA. Three sequential polymerase chain reaction were performed: ZP3 (housekeeping gene) and panfungal polymerase chain reactions, and a differentiating polymerase chain reaction based on the 5.8s ribosomal RNA and internal transcribed spacer 2 regions. The polymerase chain reaction products were then sequenced.ResultsPolymerase chain reaction identified a fungal pathogen in 20 of 64 cases (31 per cent). Aspergillus species was the most common cause of invasive fungal rhinosinusitis (nine cases). Other causes included candida (n = 4), cladosporium (n = 4), mucor (n = 1), alternaria (n = 1) and dendryphiella (n = 1) species.ConclusionPolymerase chain reaction can provide rapid identification of fungal pathogens in paraffin-embedded tissue, enabling prompt treatment of invasive fungal rhinosinusitis.